2008
DOI: 10.1182/blood-2007-08-106229
|View full text |Cite
|
Sign up to set email alerts
|

Determination of surface tissue factor thresholds that trigger coagulation at venous and arterial shear rates: amplification of 100 fM circulating tissue factor requires flow

Abstract: IntroductionPlaque rupture reveals tissue factor (TF) to flowing blood, resulting in coronary thrombosis and occlusion with consequent acute myocardial infarction. Despite the prevalence of this event, the critical concentration of surface tissue factor required to cause clotting at various hemodynamic conditions remains poorly defined. In addition, the existence, source(s), and functional activity of circulating levels of tissue factor are not fully resolved in health or disease. The function of circulating T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
120
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 32 publications
16
120
0
Order By: Relevance
“…Under flow conditions, the generation of thrombin by fibrillar collagen surfaces containing tissue factor has a moderate enhancing effect (approximately 30%) on platelet deposition, but a very large effect on fibrin deposition. 43 Additional donor-specific measurements of receptor levels, fibrinogen and VWF levels, ADP and TXA 2 release, for example, would allow for further tailoring of these parameters for in silico models of blood. Recognizing that k det collagen also coarse grains VWF function, we expect this kinetic parameter to be a function of shear rate above approximately 1500/s.…”
Section: Discussionmentioning
confidence: 99%
“…Under flow conditions, the generation of thrombin by fibrillar collagen surfaces containing tissue factor has a moderate enhancing effect (approximately 30%) on platelet deposition, but a very large effect on fibrin deposition. 43 Additional donor-specific measurements of receptor levels, fibrinogen and VWF levels, ADP and TXA 2 release, for example, would allow for further tailoring of these parameters for in silico models of blood. Recognizing that k det collagen also coarse grains VWF function, we expect this kinetic parameter to be a function of shear rate above approximately 1500/s.…”
Section: Discussionmentioning
confidence: 99%
“…26 Perfusion of blood samples at a shear rate of 1000 s −1 over microspots enriched in collagen (100 ng per microspot) resulted in a rapid formation of platelet thrombi that were rich in fibrin ( Figure 1A-1C). Lowering the collagen content (20 ng per microspot) significantly decreased platelet deposition after 7 minutes of perfusion (area covered, 12.3%±1.4% versus 33.8%±3.0%; P=0.005) and delayed the onset of fibrin formation (3 versus 5 minutes) when compared with the high collagen microspots ( Figure 1A-1C).…”
Section: Collagen-tf Surface Determines the Buildup Of Platelet-fibrimentioning
confidence: 99%
“…Kastrupet al in 2008 (17) showed that presence of bacteria, such as, Bacillus cereus and Bacillus anthracis can induce coagulation by quorum acting. Recently, a microfluidic system was used to show coagulation of blood in presence of tissue factors (TF) (37)(38)(39)(40)(41)(42). Microcontact printing was used by Okorie et al (40) to generate a surface of collagen and TF to support both platelet aggregation and coagulationin a flow chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a microfluidic system was used to show coagulation of blood in presence of tissue factors (TF) (37)(38)(39)(40)(41)(42). Microcontact printing was used by Okorie et al (40) to generate a surface of collagen and TF to support both platelet aggregation and coagulationin a flow chamber. Ismagilov and colleagues (43) generated arrays of TF patches using photolithographic techniques to study the role of diffusion in coagulation.…”
Section: Discussionmentioning
confidence: 99%